Contribution of Geophysical Data for The Prevention of Geotechnical Risks Related to Building Cracking in Agadez Region (North Niger) - Souley Baraou Idi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The seismic and magnetic data are well known for the investigation of tectonic structures and their directions on surface and subsurface, a methodological approach integrated the seismic and magnetic data interpretation combined with field measurement on cracked building and its underlying substratum, represented by Agadez sandstones and basement. The extraction of seismic lineaments from West African seismic map showed the seismic directions oriented NW-SE (N135 to N160°), passing through the studied area. The structural interpretation of magnetic map show that the Agadez region is also affected by the subsurface lineaments mainly oriented in NW-SE (N135°) directions, which are similar to the identified seismic lineaments in the same zone. A structural study carried out on the Agadez sandstones and the underlying basement, showed that faults and fractures oriented N120° to N165°, affect both the basement of the Aïr Mountains and the sandstone formations on which the city of Agadez is built. These observations showed that building cracking in Agadez region has a higher propagation tendency according to the directions ranging from NW-SE (N135°) to NNW-SSE (N165°). Therefore, the buildings cracking has a stronger propagation component according to these mean directions those are not recommended for building. To prevent and reduce the risks related to building cracking in Agadez region, it is highly recommended to build in the minor directions of cracking propagation which correspond to NE and SW directions.